2016
DOI: 10.1371/journal.pone.0167787
|View full text |Cite|
|
Sign up to set email alerts
|

Long-Circulating Curcumin-Loaded Liposome Formulations with High Incorporation Efficiency, Stability and Anticancer Activity towards Pancreatic Adenocarcinoma Cell Lines In Vitro

Abstract: The incorporation of hydrophobic drugs into liposomes improve their bioavailability and leads to increased stability and anticancer activity, along with decreased drug toxicity. Curcumin (Cur) is a natural polyphenol compound with a potent anticancer activity in pancreatic adenocarcinoma (PA). In the present study, different types of Cur-loaded liposomal formulations were prepared and characterized in terms of size, shape, zeta potential, optimal drug-to-lipid ratio and stability at 4°C, 37°C; and in human pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 55 publications
2
32
0
1
Order By: Relevance
“…Conversely, the size of liposomes stored at 25°C was almost unchanged over time. Moreover, the zeta potential of liposomes produced using the 3DPM-C/Tape rector (at FRR of 25 and TFR of 1 ml/min) was -15.06 mV, which is coherent with the literature [27].…”
Section: Synthesis Of Liposomessupporting
confidence: 89%
“…Conversely, the size of liposomes stored at 25°C was almost unchanged over time. Moreover, the zeta potential of liposomes produced using the 3DPM-C/Tape rector (at FRR of 25 and TFR of 1 ml/min) was -15.06 mV, which is coherent with the literature [27].…”
Section: Synthesis Of Liposomessupporting
confidence: 89%
“…Curcumin has exhibited anticancer effects via inducing apoptosis in a variety of cancers. The apoptosis induced by curcumin leads to the morphological alternations of cancer cells, including cell shrinkage, cytoplasmic blebbing, irregularity in shape, and externalization of cell membrane phosphatidylserine [ 88 ]. The apoptosis mechanism of curcumin involves certain biomolecules and several signal pathways [ 89 ].…”
Section: Health Benefits Of Curcuminmentioning
confidence: 99%
“…These results were consistent with those of previous studies showing that curcumin inhibits the anti-apoptotic protein and regulates the pro-apoptotic protein. 23 The inhibitors of NF-κB expose the cancer cells to apoptosis. 24 A previous study reported that the administration of 100 pg of 17-β estradiol could increase NF-κB expression in CMH trophoblast cells cultures.…”
Section: Discussionmentioning
confidence: 99%